2016
DOI: 10.1139/gen-2015-0132
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation in the genus Avena

Abstract: Abstract:Genome size is an indicator of evolutionary distance and a metric for genome characterization. Here, we report accurate estimates of genome size in 99 accessions from 26 species of Avena. We demonstrate that the average genome size of C genome diploid species (2C = 10.26 pg) is 15% larger than that of A genome species (2C = 8.95 pg), and that this difference likely accounts for a progression of size among tetraploid species, where AB < AC < CC (average 2C = 16.76, 18.60, and 21.78 pg, respectively). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 64 publications
(90 reference statements)
11
58
0
Order By: Relevance
“…In Knautia , the results of ploidy and genome size of 23 species indicated that genome size of tetraploid K. arvernensis and hexaploid K. ressmannii is approximately 1.8-fold and approximately 2.7-fold than diploid K. calycina , respectively41. Similar results of the genome size being inconsistent with the ploidy level were also observed in Chenopodium 42 and Avena 43. One likely reason for this phenomenon is that some genes or chromosome fragments with functional redundancy had not doubled in a genome duplication event, or they were deleted after genome duplication event44.…”
Section: Discussionmentioning
confidence: 69%
“…In Knautia , the results of ploidy and genome size of 23 species indicated that genome size of tetraploid K. arvernensis and hexaploid K. ressmannii is approximately 1.8-fold and approximately 2.7-fold than diploid K. calycina , respectively41. Similar results of the genome size being inconsistent with the ploidy level were also observed in Chenopodium 42 and Avena 43. One likely reason for this phenomenon is that some genes or chromosome fragments with functional redundancy had not doubled in a genome duplication event, or they were deleted after genome duplication event44.…”
Section: Discussionmentioning
confidence: 69%
“…Though less pronounced, this trend was also observed in the consensus map and each of its component maps (Chaffin et al., ). Indirect evidence (since no extant D genome diploid is known) suggests that the D genome has the smallest physical size of the component genomes in hexaploid or tetraploid oat (Yan et al., ). However, physical chromosome size does not necessarily correlate with recombination distance or even with the number of polymorphic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence (since no extant D genome diploid is known) suggests that the D genome has the smallest physical size of the component genomes in hexaploid or tetraploid oat (Yan et al, 2016a).…”
Section: Comparative Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, the monoploid genome size of polyploids is usually lower than that of their diploid or lower polyploid relatives due to a selective force or endogenous mechanisms favouring DNA loss after polyploidization (Leitch & Bennett, 2004;De Smet et al, 2013). The prevalent trend towards genome downsizing correlated with increasing ploidy level in polyploid series of closely related species (or within species) has been repeatedly confirmed in many plant genera, most recently, for example, in Aloe L. (Rao et al, 2015), Avena L. (Yan et al, 2016), Calligonum L. (Gouja et al, 2015), Chrysanthemum L. (Luo et al, 2017), Festuca L. (Ezquerro-L opez et al, 2017), Fragaria L. (Nosrati, 2015), Knautia L. , (Meudt et al, 2015). Considering this general trend, the opposite patterns observed in the Alyssum species under study could be attributed to the fact that they are not each others' closest relatives (Zozomov a-Lihov a et al, 2014;Spaniel et al, 2017a); however, there are also other possible explanations.…”
Section: Ploidy Levels and Genome Size Variationmentioning
confidence: 96%